Rojena v narečje: akademikinji prof. dr. Zinki Zorko ob 80-letnici (University of Maribor Press, 2015)
Born in Dialect: For Academician prof. dr. Zinka Zorko at the 80th Anniversary. Academician Zinka Zorko belongs to the generation of Slovene Slavists who, according to Ramovš, Logar and Rigler, established the foundations of Slovenian dialectology. Her scientific research work (603 discussions, articles, independent chapters in monographs and proceedings, reviews, reviews, etc.) is focused on exploring the "white spots" on the dialectological map of Slovenia; She is the best expert and researcher of Carinthian, Styrian and Pannonian dialects and speeches. Zinka Zorko is one of the few linguists who can boast about her school, t. i. Maribor dialectological school, where he and his students have a decisive influence on the development of contemporary European dialectology. At her school, grammars of individual speeches are created that explain the dialectal diversity of the Slovenian language, and dialectological studies of white spots on the map of dialectal features of the Slovene language draw new more precise dialectal boundaries. Academician Zinka Zorko: (1) moved the border between the Styrian and Carinthian speeches in the east into the Drava valley to Fala and Ruš, to which the basic East Carinthian sub-vowel composition extends; (2) demarcate the Goat and Slovenian linguistic space; (3) taking into account the linguistic influences in the Slovenian border dialects, discovered and explained stronger Slovene influences on the German border of Styria - discovered new as well as transitional and intermediate speeches beyond and beyond the national borders; (4) directed the research to the Radgonski kot, (5) to the Slovenian-Hungarian border (Porabje) and (6) the Slovenian-Croatian area (Haloze, Rogatec, Bizeljsko). Science is advancing in quick steps, the amount of information is multiplying day by day. This in us awakens the capacity for wonder, for true joy in finding and discovering something new. We humans are cognitively committed to science and the arts. Every true scientist is in some way an artist of Life, and every true artist is a scientist of soul, heart and spirit. Science today faces greater moral responsibility than ever before; he can do an incredible amount, and the real question is if he can do it all! All the sciences, especially the natural sciences, speak some universal language of the world, yet every scientist, as an individual and as a person, carries within him a specific language of the space from which he originates; it is the space of his narrower homeland, the space of his heart and tongue, the place of his dreams and a hearty memory of his ancestors. As Slavists, at this solemn moment, the thought escapes us into our millennial fate of our mother tongue - from the Bruges monuments to the present. We are small and have existed among the big ones. We differ from small and big again because of our language. So let’s be proud of our mother tongue, our own Slovenian language. We defend his dignity and sovereignty by speaking Slovenian and writing at all levels of existence, and joyfully dreaming of our dialect as well. And let’s be honest, honest, compassionate and solidary in everything. So let’s be grateful and cheerfully excited researchers of Life. In our Slovenian and universal way. Let’s do good, protect ourselves from the bad and love each other!